ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN PENGGUNA HOTSPOT (WIFI) (Studi Kasus Mahasiswa Fakultas Ekonomi Universitas Katolik Santo Thomas Sumatera Utara) - Sagala, Roslinda (Jurnal Manajemen dan Bisnis, 2016)
The purpose of this study to analyze the effect of signal coverage hotspot (wifi), ease of access hotspots (wifi), access speed hotspot (wifi), and the comfort of hotspot access (wifi) and simultaneous partial effect on the level of user satisfaction. To determine whether the most influential factor / dominant on the level of user satisfaction hotspot (wifi) in the Faculty of Economics, Catholic University of St. Thomas SU. The benefits of this study, those authors. Comparing theories - theories that have been explored for this through research conducted, as well as develop analytical and critical thinking skills to the problems that exist, For private university. As input and consideration for Private Higher Education to develop the quality of education as an institution of higher education with the needs and desires of students. Total sample of 45 respondents, the method of collecting data through questioner and documentation, methods of data analysis by factor analysis. The results showed that: Coverage hotspot signal (wifi). These variables have a dominant influence on the level of user satisfaction hotspot (wifi) in the Faculty of Economics of St. Thomas Catholic University of North Sumatra. Ease of access hotspots (wifi) proved to be the dominant influence on the level of user satisfaction hotspot (wifi) in the Faculty of Economics of St. Thomas Catholic University of North Sumatra. Students are quite satisfied with the speed of hotspot access (wifi). These variables proved the dominant influence on the level of user satisfaction hotspot (wifi) within the Faculty of Economics, Catholic University of St. Thomas North Sumatra. Influence comfort hotspot access (wifi) on the level of user satisfaction hotspot (wifi). Based on the data that has been processed and analyzed, it can be concluded that the comfort of the hotspot access (wifi) has dominant influence on the level of user satisfaction hotspot (wifi) Variable comfort hotspot access (wifi) positive effect on the level of user satisfaction hotspot (wifi). Thus increasing the speed of hotspot access (wifi) will be followed by increased user satisfaction. Based on the research results Party IT Santo Thomas Catholic University of North Sumatra should maintain speed hostpot access (wifi). Researchers further should expand the scope of survey respondents, not only at the Faculty of Economics, Catholic University of St. Thomas North Sumatra, but it could be in the Faculty - other faculties. Researchers should be able to further expand variables - variables examined, because it is possible there are many factors - other factors that could affect user satisfaction hotspot (wifi).